Child-Friendly School and Its Relationship with the Merdeka Curriculum in Forming the Students' Character through Science Learning - Rusilowati, A.; Hidayah, I.; Nugrahani, R.; Abidin, Z.; Hutagalung, F. D.; Sofchah, T.; Ariyanti, S. W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2024)
The Merdeka Curriculum demands student competence and character formation through the Pancasila Student Profile (called P3). Through science learning, P3 indicators can be achieved. This study aims to (1) analyze Child-friendly School (CFS) implementation in SHS-X, (2) analyze SHS-X students' characters, and (3) identify teachers' attitudes during learning in SHS-X. This research uses a qualitative approach. The sample was obtained using purposive sampling from a child-friendly school implementing a Merdeka curriculum. The data validity was tested by triangulation. Data was explored based on participants' said, felt, and done or an emic perspective. Science learning activities inside and outside the classroom were observed. The subjects were principals, teachers, alumni, parents, and students at SHS-X. Data was collected through observation, interviews, analyzing documents, and giving questionnaires. Data analysis used the Miles and Huberman model. Based on the research and discussion results, implementing the child-friendly school policy at SHS-X has met the indicators set out in the Child-Friendly School Guidelines. The characters formed in SHS-X students include (1) nationalism, (2) religion, (3) leadership, (4) politeness, (5) honesty, (6) cooperation, and (7) anti-corruption. Another thing that makes SHS-X superior is that the teachers’ attitudes during learning are friendly, humane, and fun. With the two-way discussion method, learning becomes more interactive. With teachers teaching humanely, many students experience changes in behavior and learning outcomes. It is hoped that SHS-X's best practices in implementing CFS can inspire other schools.